Equity and effectiveness of optimal taxation in contests under an all-pay auction - Yosef Mealem; Shmuel Nitzan (Center for Economic Studies and ifo Institute (CESifo), 2012)
The means of contest design may include differential taxation of the prize. This paper establishes that, given a revenue-maximizing contest designer who faces a balanced-budget constraint, the optimal taxation scheme corresponding to an all-pay auction is appealing in two senses. First, it ensures exceptional equitable final prize valuations. Second, it is effective; it yields total contestants' efforts that are larger than those obtained under almost any Tullock-type lottery. Furthermore, when a budget surplus is allowed, the superiority of optimal taxation under the APA is preserved in terms of equity and effectiveness relative to optimal taxation under any contest success function.
Keywords: D70; D72; D74; D78; 330; contest design; revenue maximization; balanced-budget constraint; budget surplus; optimal differential taxation; endogenous stakes; all-pay auction; lottery; Glücksspiel; Optimale Besteuerung; Auktionstheorie; Einnahmen; Theorie